Respuesta :
Na2SO4 + Pb(NO3)2 --> NaNO3 + PbSO4
Na2SO4 + Pb(NO3)2 --> 2NaNO3 + PbSO4
(i'm not sure if you need to add the forms of the compounds as well)
Na2SO4 + Pb(NO3)2 --> 2NaNO3 + PbSO4
(i'm not sure if you need to add the forms of the compounds as well)
Explanation:
A reaction equation that shows same number of atoms on both reactant and product sides is known as a balance equation.
[tex]Na_{2}SO_{4} + Pb(NO_{3})_{2} \rightarrow NaNO_{3} + PbSO_{4}[/tex]
Number of atoms on reactant side are as follows.
Na = 2
[tex]SO_{4}[/tex] = 1
Pb = 1
[tex]NO_{3}[/tex] = 2
Number of atoms on product side are as follows.
Na = 1
[tex]SO_{4}[/tex] = 1
Pb = 1
[tex]NO_{3}[/tex] = 1
Therefore, to balance this chemical equation we multiply [tex]NaNO_{3}[/tex] by 2 on product side. Thus, we can conclude that the balanced chemical equation will be as follows.
[tex]Na_{2}SO_{4} + Pb(NO_{3})_{2} \rightarrow 2NaNO_{3} + PbSO_{4}[/tex]